THE EFFECT OF MUSIC THERAPY ON SLEEP QUALITY AMONG CHILDREN WITH CHRONIC ILLNESS: DOI: https://doi.org/10.35654/ijnhs.v2i1.51 - Resi Putri Naulia; Allenidekania Allenidekania; Happy Hayati (Alta Dharma Publisher, 2019)
Abstract The priority of handling children with chronic illness is to improve the quality of life by paying attention the symptoms that arise during treatment, one of which is the sleep problem. The purpose of this study to identify the effect of music therapy for the sleep quality of children with chronic illness. This study used a quasi experiment. Sample size was 30 childrens were divided into experimental group and control group. Respondents were given music therapy in 30-45 minutes before bed for 4 days. Sleep quality is measured by using Pittsburgh Sleep Quality Index (PSQI). There was a significant mean difference regarding PSQI score in experimental and control group. It was found that the experimental group score was higher compared with the control group (p=0,001). Thus music therapy could be used as an alternative intervention to improve the sleep quality to improve the quality of life of children with chronic illness. Key words : children, chronic illness, music therapy, sleep quality